2009
DOI: 10.1117/12.815650
|View full text |Cite
|
Sign up to set email alerts
|

Active sensing of fatigue damage using embedded ultrasonics

Abstract: Embedded ultrasonics has demonstrated considerable utility in structural health monitoring of aeronautical vehicle. This active sensing approach has been widely used to detect and monitor cracks, delaminations, and disbonds in a broad spectrum of metallic and composite structures. However, application of the embedded ultrasonics for active sensing of incipient damage before fracture has received limited attention. The aim of this study was to investigate the suitability of embedded ultrasonics and nonlinear ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…We know that the resonant frequency, as an intrinsic parameter of the structural dynamics, is widely accepted as a critical damage evaluation index. Although the value might vary with the shape, dimension, material property, and testing frequency band, the results of our and others’ experiments have all demonstrated that the Δf value corresponding to the early-stage damage of a dog-bone sample was about 10 −1 kHz (Li et al, 2012; Palomino et al, 2011; Zagrai et al, 2009). For the ASS sample used in previous work, the sub-millimeter crack damage and a plastic deformation zone around the pre-notch resulted a 0.2–0.3 kHz peak frequency decrease (Luo et al, 2013).…”
Section: Resultsmentioning
confidence: 50%
See 3 more Smart Citations
“…We know that the resonant frequency, as an intrinsic parameter of the structural dynamics, is widely accepted as a critical damage evaluation index. Although the value might vary with the shape, dimension, material property, and testing frequency band, the results of our and others’ experiments have all demonstrated that the Δf value corresponding to the early-stage damage of a dog-bone sample was about 10 −1 kHz (Li et al, 2012; Palomino et al, 2011; Zagrai et al, 2009). For the ASS sample used in previous work, the sub-millimeter crack damage and a plastic deformation zone around the pre-notch resulted a 0.2–0.3 kHz peak frequency decrease (Luo et al, 2013).…”
Section: Resultsmentioning
confidence: 50%
“…The material mechanical damage behavior evaluated by EMI technique has been reported by several researchers (Giurgiutiu et al, 1999;Soh, 2010, 2011;Palomino, 2011;Park et al, 2010;Sevostianov et al, 2010;Zagrai et al, 2009). Aluminum alloys were widely used because of its high availability and the low price.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two methods were used to interpret the data. The linear frequency shift metric used by Zagrai et al (2009) and was applied to the peak responses of the low and high frequency HP4192A measurements, and the fundamental frequency RITEC-Shunt measurements. An average amplitude metric was applied to all measurements, including the RITEC-Shunt second harmonic measurements, to determine the effect of fatigue on measurement amplitude.…”
Section: Plate Test 2 -Resultsmentioning
confidence: 99%